2019
DOI: 10.1136/neurintsurg-2018-014452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of balloon guide catheter on clinical outcomes and reperfusion in Trevo thrombectomy

Abstract: IntroductionThe Solitaire stent retriever registry showed improved reperfusion, faster procedure times, and better outcome in acute stroke patients with large vessel occlusion treated with a balloon guide catheter (BGC) and Solitaire stent retriever compared with a conventional guide catheter. The goal of this study was to evaluate whether use of a BGC with the Trevo stent retriever improves outcomes compared with a conventional guide catheter.MethodsThe TRACK registry recruited 23 sites to submit demographic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 26 publications
4
40
3
Order By: Relevance
“…In agreement with previous studies, complete recanalization (mTICI 3, 62.5%) was commonly achieved in our series [ 18 ]. Nevertheless, the reported rates of complete recanalization using BGC have ranged from 15 to 63% [ 8 , 19 , 20 ]. We believe that these differences can be accounted for in part by differences in BGC use in the patients in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with previous studies, complete recanalization (mTICI 3, 62.5%) was commonly achieved in our series [ 18 ]. Nevertheless, the reported rates of complete recanalization using BGC have ranged from 15 to 63% [ 8 , 19 , 20 ]. We believe that these differences can be accounted for in part by differences in BGC use in the patients in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, identifying anatomical determining factors restricting the effectiveness of MT represents an initial step towards adapting the endovascular strategy and techniques to the anatomical conditions of patients for more efficient clot extraction. While one study did report target location in the distal ICA [ 8 ], specific BGC positioning for mechanical thrombectomy has seldom been described [ 5 , 7 , 18 20 ]. Our study revealed an efficacy gradient depending on the location of the BGC in the carotid artery, consistent with the results of Jeong et al [ 13 ] (TICI 3 irrespective of passes in 67% of the distal BGC group versus 45% for the proximal BGC group).…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing mechanical thrombectomy for acute ischemic stroke secondary to large vessel occlusion who require a fewer number of passes to achieve successful reperfusion have better functional outcomes than patients who undergo a higher number of passes 1 2. First-pass effect has thus been used as a primary radiographic outcome measure in large studies 3–5. It has also been well established that successful reperfusion predicts outcome and is protective against symptomatic intracranial hemorrhage (sICH), which is associated with worse clinical outcomes after thrombectomy 6 7.…”
Section: Introductionmentioning
confidence: 99%
“…39 This improves reperfusion times and quality, and, most importantly, patient outcome. [40][41][42][43] After the BGC is placed in the cervical ICA (►Fig. 1), a microcatheter is advanced over a microwire through a large bore distal access catheter (DAC).…”
Section: Triaxial Setup: Balloon Guide Catheter Large Bore Distal Acmentioning
confidence: 99%